RELIABILITY OF EC 155 B1 AIRCRAFT COMPONENTS USING UPPER CONTROL LIMIT (ALERT LEVEL) FORMULATION - Ramadhan Adil Labib (Vortex, 2020)
To provide a reliability and service from PT. Indonesia Air Transport & Infrastructure, operators have to make sure the condition of all the systems and the components of EC 155 B1 is serviceable. However, there is still a bunch of unusual repetitive defect that recorded and mostly it came from the most critical system that can occur an incident at any time. In this study discussed on EC 155 B1’s component Reliability Analysis Method Using Reliability Control Program (RCP), Reliability Control Program is the reliability of aircraft system by determining which component that has to be concern by define the Upper Control Limits (Alert Value). From the calculation of RCP, ATA Chapter 62 Main Rotor is the most defected.